Efeitos do atipamezol e da ioimbina isolados ou em associação com a naloxona nda reversão anestésica de macacos bugios (Aloautta guariba clamitans) (CABRERA, 1940) anestesiados com metadona, dexmedetomidina e cetaminha S(+) - Monteiro, Sharlenne Leite da Silva [UNESP] (2015)
The present study addressed the effects caused by chemical restraint with methadone (0.1mg/kg), dexmedetomidine (5µg/kg) and ketamine S(+) (8 mg/kg) in Howley monkeys (Alouatta guariba clamitans) as well as the comparison of the quality and the time of the anesthetic reversal with isolated or associated narcotic α2-adrenergic antagonists in New world monkeys. Five adult and healthy Howley monkeys were used. The anesthetic protocol was administered via intramuscular. Five minutes after sedation, the animal was put on a table with thermal mattress where the following parameters were measured: cardiac and respiratory frequencies, rectal temperature, systolic arterial pressure and palpebral reflexes. These parameters were measured every 10 minutes. After 45 minutes of anesthesia a solution of NaCl 0.9% was administered to the control treatment, 25µg/kg of atipamezole for the ATI treatment, 0.5 mg/kg of yohimbine to the IOI treatment, atipamezole (25µg/kg) associated with naloxone (0.2 mg/kg) to the ATINALOX treatment and the IOINALOX treatment was composed of yohimbine (0.5 mg/kg) associated with naloxone (0.2 mg/kg), administered via intravenous in the primates' ulnar vein. After the reverser administration the animal was placed on a cage and the period of full recovery was evaluated by three researchers. The period of full recovery was determined from the antagonist administration until the patient's full recovery. The recovery was evaluated using scores that varied from zero (0) to three (3), accordingly to Galante, 2013. Some animals showed drooling after the intravenous administration of atipamezole and yohimbine. The association of methadone, dexmedetomidine and ketamine was effective to the chemical restraint of these animals allowing the performance of clinical procedures by up to 45 minutes. The IOINALOX treatment was the most effective regarding to time but the ATINALOX treatment gained the best recorvery